Characterization of umami-active and volatile compounds in Mekai (Pycnarrhena tumefacta miers) leaves from Kalimantan using LC-HRMS, GC-MS, and electronic tongue - Nur Amaliah; Salengke Salengke; Zainal Zainal; Meta Mahendradatta (Discover Food)
Abstract This study investigates the umami-related compounds, volatile components, and sensory attributes of Mekai (Pycnarrhena tumefacta miers) leaves based on maturity level and extraction solvent. The research examines free protein and free glutamate levels as umami indicators. Key metabolites, volatile chemicals, umami-related chemical changes, and intensity of taste were found utilizing liquid chromatography-high resolution mass spectrometry (LC-HRMS), gas chromatography-mass spectrometry (GC-MS), and an electronic tongue. The metabolite profiles varied between young and old leaves, as well as between water and methanolic extracts. Both leaf types exhibited low umami intensity, with 7 umami-related compounds detected in the water extract and 3 in the methanolic extract. Identified umami compounds included amino acids, peptides, nucleotides, and organic acids. Volatile analysis revealed aldehydes, particularly 4-hydroxy-3-methyl-butanal and butanal, as dominant components. Analysis showed the highest free protein (75.4 mg/mL) and free glutamate (10.3 µg/mL) concentrations in old leaves extracted with water. These findings provide insights into selecting Mekai leaves and extraction methods for umami enhancement. Further processing is necessary to enhance their umami intensity for potential application as a natural plant-based flavoring alternative.